PENGELOLAAN WAKAF TUNAI DI LEMBAGA PENGELOLA WAKAF DAN PERTANAHAN PENGURUS WILAYAH NAHDLATUL ULAMA DAERAH ISTIMEWA YOGYAKARTA - Fahham, Achmad Muchaddam (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2015)
One of cash waqf management agency in Yogyakarta is Endowments and Land Management Agency Regional Board of Nahdlatul Ulama Yogyakarta. Since the year 2011, this institution has manage cash waqf to increase well-being of Muslims in the area. This study aimed to describe the reason that prompted the agency to manage cash endowments, accumulation, investment and distribution. This research is qualitative. Data were collected through library research, focus group discussions and in-depth interviews with managers the Institution of Waqf and Land Management Agency Regional Board of Nahdlatul Ulama Yogyakarta. The collected data analyzed by means of categorization, classification, and reduction, after that it concluded in accordance with the objectives of the study. The study concluded there are three reasons that drive Endowments and Land Management Agency Regional Board of Nahdlatul Ulama Special Region of Yogyakarta to manage cash endowments, namely theological, sociological and juridical reasons. Raising cash waqf is done in two stages: socialization and certification endowments. Endowments have accumulated cash is invested in deposits at the Bank Syariah BPD Yogyakarta. The value of the benefits derived from the investment funds used as a productive loan without interest. The loan funds must be returned to the Endowment and Land Management Agency PW NU DIY, so that these funds can be used by other borrowers in need. In practice, no loans were not paid off, because the refund of the loan without interest and administrative costs. In addition, the values of the benefits gained from the deposits are also used for education and health assistance.